A preclinical model of THC edibles that produces high-dose cannabimimetic responses - Anthony English; Fleur Uittenbogaard; Alexa Torrens; Dennis Sarroza; Anna Veronica Elizabeth Slaven; Daniele Piomelli; Michael R Bruchas; Nephi Stella; Benjamin Bruce Land (eLife, 2024)
No preclinical experimental approach enables the study of voluntary oral consumption of high-concentration Δ9-tetrahydrocannabinol (THC) and its intoxicating effects, mainly owing to the aversive response of rodents to THC that limits intake. Here, we developed a palatable THC formulation and an optimized access paradigm in mice to drive voluntary consumption. THC was formulated in chocolate gelatin (THC-E-gel). Adult male and female mice were allowed ad libitum access for 1 and 2 hr. Cannabimimetic responses (hypolocomotion, analgesia, and hypothermia) were measured following access. Levels of THC and its metabolites were measured in blood and brain tissue. Acute acoustic startle responses were measured to investigate THC-induced psychotomimetic behavior. When allowed access for 2 hr to THC-E-gel on the second day of a 3-day exposure paradigm, adult mice consumed up to ≈30 mg/kg over 2 hr, which resulted in robust cannabimimetic behavioral responses (hypolocomotion, analgesia, and hypothermia). Consumption of the same gelatin decreased on the following third day of exposure. Pharmacokinetic analysis shows that THC-E-gel consumption led to parallel accumulation of THC and its psychoactive metabolite, 11-OH-THC, in the brain, a profile that contrasts with the known rapid decline in brain 11-OH-THC levels following THC intraperitoneal (i.p.) injections. THC-E-gel consumption increased the acoustic startle response in males but not in females, demonstrating a sex-dependent effect of consumption. Thus, while voluntary consumption of THC-E-gel triggered equivalent cannabimimetic responses in male and female mice, it potentiated acoustic startle responses preferentially in males. We built a dose-prediction model that included cannabimimetic behavioral responses elicited by i.p. versus THC-E-gel to test the accuracy and generalizability of this experimental approach and found that it closely predicted the measured acoustic startle results in males and females. In summary, THC-E-gel offers a robust preclinical experimental approach to study cannabimimetic responses triggered by voluntary consumption in mice, including sex-dependent psychotomimetic responses.